Does Recognition versus Disclosure Affect Debt Contracting? Evidence from SFAS 158 - Donovan, John B.; McMartin, Andrew S.; Phillips, Matthew A. (The Accounting Review, 2024)
ABSTRACT We study whether recognition versus disclosure affects debt contracting using SFAS 158 as a setting. Upon recognition of previously disclosed pension liabilities, we find that debt contracts of firms that have high pension underfunding contain relatively more covenants based on the balance sheet and a lower cost of debt. Additional analysis suggests that improved reliability of recognized information is a likely mechanism for these findings. We also document that recognition did not affect the credit risk of the borrower or the use of income statement–based covenants that were unaffected by the accounting standard change. Collectively, our evidence suggests that recognition of previously disclosed accounting information can facilitate the incorporation of that information into lenders’ screening and monitoring. Data Availability: Data used in this study are available from public sources identified in the study.